Chemical profiling and clustering of Piperaceae revealed by volatilomics analysis - Hariani, Sulifah Aprilya; Asyiah, Iis Nur; Prayitno, Trio Ageng (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
The Piperaceae family is one of the aromatic plants that have a distinctive odor and is known to have tremendous benefits in human life. Piperaceae is used as raw material for medicines, spices, antibacterial, antiviral, and insecticides. Research on the composition of volatile chemical compounds in Piperaceae members is still limited. This study aims to extract volatile chemical compounds in the Piperaceae family and classify Piperaceae members based on their volatile compounds. The type of research is laboratory research. The research samples were leaves of ten species of Piperaceae members, namely Piper cubeba, P. nigrum, P. betle, P. ornatum, P. retrofractum, P. sarmentosum, Peperomia pellucida, Peperomia scandens, Peperomia caperata, and Peperomia maculosa. The research instrument was an observation sheet of SPME-GCMS analysis results. Data in the form of metabo-analysis was obtained from laboratory analysis using SPME-GCMS by producing a comprehensive volatile compound profile of the Piperaceae family and revealing differences between species. The results of SPME-GCMS analysis on the Piperaceae family obtained 197 identified volatile chemical compounds. The largest group of chemical compounds in 10 species of the family consists of sesquiterpene (16.2%), monoterpene (11.7%), sesquiterpenoid (7.1%), alcohol (6.1%), aldehyde (4.6%), terpene (4.1%), terpenoid (4.1%), alkene (3%), fatty acid (2.5%), ketone (2.5%), phenol (2.5%), alkane (2%) and other groups less than 2%. Characteristics of typical compounds in the genus Peperomia amounted to 10, namely Alpha-pinene, (-)-; Camphene; 2-beta-pinene; l-Limonene; Nonanal; (-)-.beta.-Elemene; alpha.-Copaene; Germacrene D; cis-caryophyllene; Bicycloelemene. In the genus Piper, the variation in the character of volatile chemical compounds is very large, typical characteristics possessed by 6 Piper species are alpha-pinene, (-)-; alpha.-Copaene; alpha.-Humulene; (-)-beta.-Elemene; and trans-Caryophyllene. The study concluded that 197 volatile compounds from 10 Piperaceae species had been identified. The results of this study can be recommended that the Piperaceae family can be optimized for public health.